The hockey-stick association of energy supply in the first 72 h of critical illness may apply only to patients with a normal body mass index: a post-hoc analysis of a prospective observational multicenter study - Wang, Youquan; Wang, Yanjuan; Fu, Yao; Bao, Lingling; Zhang, Dong; Li, Hongxiang (Frontiers in Nutrition, 2026)
ObjectiveIt is unclear whether this non-linear relationship between caloric delivery during the acute phase of critical illness and prognosis applies to patients across all body mass index (BMI) categories.MethodsThis secondary analysis of a multicenter prospective observational study included patients with acute gastrointestinal injury (AGI) who were admitted to the intensive care unit (ICU) for at least 3 days. The patients were divided into two subgroups based on BMI: normal BMI and overweight (BMI: 25–30 kg/m2). We used univariate and multivariate Cox regression analyses to investigate the relationship between calorie delivery within the first 72 h of ICU admission and 28-day mortality and to explore whether a non-linear relationship exists between the two.ResultsA total of 361 AGI patients were included in the final analysis, including 272 in the normal BMI subgroup and 89 in the overweight subgroup. In the normal BMI subgroup, Cox regression analysis revealed a significant non-linear relationship (p = 0.003) and association (p = 0.002) between daily delivered calories and 28-day mortality. Increasing the daily delivered calories from 0 to 18 kcal/kg/day was associated with decreasing mortality (hazard ratio [HR] 0.892, 95% CI: 0.816–0.975), while the daily delivered calories > 18 kcal/kg/day were associated with increasing mortality (HR: 1.116, 95% CI: 1.016–1.227). In the overweight subgroup, an increase in daily delivered calories was also associated with higher mortality (HR: 1.124, 95% CI: 1.043–1.211, p = 0.003). However, the overall non-linear relationship between daily delivered calories and mortality disappeared (p = 0.466). Notably, increasing the daily delivered calories from 15 to 25 kcal/kg/day was associated with increased mortality (HR: 1.160, 95% CI: 1.030–1.306). After adjusting for potential confounders through a multivariable Cox regression analysis, the results remained robust.ConclusionThe association between daily delivered calories within the first 72 h of ICU admission and 28-day mortality in critically ill patients showed a hockey-stick association, which was observed only in patients with a BMI of 18.5–24.9 kg/m2. However, no similar relationship was found in patients with a BMI of 25–30 kg/m2. These findings should be interpreted as exploratory and hypothesis-generating, and further studies are needed to confirm and extend these observations.